HUBUNGAN ANTARA KECEMASAN DENGAN KUALITAS TIDUR PADA MAHASISWA YANG SEDANG MENGERJAKAN SKRIPSI DI UNSIQ - Lutfiatul Qonita; Romdiyah Romdiyah; Anisa Ell Raharyani; Fifi Alviana (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Anxiety can be interpreted as a feeling of fear or worry, which is unclear or vague. When a person experiences an anxiety disorder, it can be seen from his behavioral, emotional, cognitive, and physiological responses. The purpose was finding out the relationship between anxiety and sleep quality in students who are working on their thesis at UNSIQ. The type of research used is quantitative research using a cross sectional approach with a population of 29 respondents. This study usesd the chi-square test to examine the relationship between variables. The results showed the characteristics of the respondents were mostly 22 years old (69%), female gender 20 respondents (69%), anxiety level 14 respondents (48.3%), sleep quality 22 respondents (75.9%), chi-square test obtained a p-value of 0.030 (α <0.05).